Gestational Anemia and Severe Acute Maternal Morbidity: A Population-based Study. Issue 4 (December 2021) - Guignard, J.; Deneux-Tharaux, D.; Seco, A.; Beucher, G.; Kayem, G.; Bonnet, M.P.
Abstract : ( Anaesthesia . 2021;76:61–71) Gestational anemia (GA) has been associated with preterm birth, low birth weight, and maternal morbidity. However, the connection between maternal morbidity and GA is based on studies that focused on specific maternal complications, used interventions as proxies for complications, or lacked data about the timing of anemia and severe maternal complication. This prospective, population-based study aimed to investigate the association between GA and severe acute maternal morbidity (SMM).